Detecting filamentary pattern in the cosmic web: a catalogue of filaments for the SDSS. Issue 4 (21st January 2014) - Tempel, E.; Stoica, R. S.; Martínez, V. J.; Liivamägi, L. J.; Castellan, G.; Saar, E.
Abstract: The main feature of the spatial large-scale galaxy distribution is its intricate network of galaxy filaments. This network is spanned by the galaxy locations that can be interpreted as a three-dimensional point distribution. The global properties of the point process can be measured by different statistical methods, which, however, do not describe directly the structure elements. The morphology of the large-scale structure, on the other hand, is an important property of the galaxy distribution. Here, we apply an object point process with interactions (the Bisous model) to trace and extract the filamentary network in the presently largest galaxy redshift survey, the Sloan Digital Sky Survey (SDSS). We search for filaments in the galaxy distribution that have a radius of about 0.5 h −1 Mpc. We divide the detected network into single filaments and present a public catalogue of filaments. We study the filament length distribution and show that the longest filaments reach the length of 60 h −1 Mpc. The filaments contain 35–40 per cent of the total galaxy luminosity and they cover roughly 5–8 per cent of the total volume, in good agreement with N -body simulations and previous observational results.